PELATIHAN PEMBUATAN HAND SANITIZER BAGI MASYARAKAT KELURAHAN TELUK LERONG ULU DAN BUGIS, SAMARINDA - Reksi Sundu; Henny Nurhasnawati; Eka Siswanto Syamsul; Rio Adi Saputra (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Health is an important aspect of life. According to the World HealthOrganization (WHO), hand hygiene is one of the most important steps to prevent and control the spread of disease (maintaining health). At the time of activity, hands are often contaminated with microorganisms because the hands are an intermediary for the entry of microbes into the digestive tract. The purpose of this activity is to provide education to the community, especially those in TelukLerong Ulu and Bugis Villages about how to make hand sanitizer. The method of this activity is lecture, discussion and training. Community service activities in TelukLerong Ulu and Bugis Villages on June 24, 2020 went smoothly and received a good response. Each participant brought home their own homemade product.